P-020 Clinical Outcomes Associated with Non-medical Switching or Discontinuation of Anti-TNF Inhibitors Among Patients with Inflammatory Bowel Disease. (March 2016) - Wolf, Doug; Skup, Martha; Yang, Hongbo; Faust, Elizabeth; Fang, Anna; Chao, Jingdong; Lebwohl, Mark
Abstract : Background: Inflammatory bowel disease (IBD), which includes both Crohn's disease (CD) and ulcerative colitis (UC), is a chronic condition characterized by inflammation of the gastrointestinal tract. Patients with IBD are often treated with anti-tumor necrosis factor (TNF) agents. However, patients with a stable response to anti-TNF therapy may discontinue or switch treatments for non-medical reasons such as cost reduction. We evaluated real-world clinical outcomes associated with non-medical switching of anti-TNF therapies among patients with IBD in the United States. Methods: An online, physician-administered chart review was used to collect data on patients with a diagnosis of CD or UC who had response for ≥6 months to an anti-TNF therapy. Gastroenterologists selected 2 cohorts that were matched based on primary diagnosis: (1) patients who discontinued or switched from the anti-TNF on which they achieved response for non-medical reasons (switchers/discontinuers) and (2) patients who did not discontinue for non-medical reasons (continuers). Switchers/discontinuers were followed for 12 months from the date of discontinuation (index date); continuers were followed for 12 months from the date of an office visit within 2 months of the matched switcher/discontinuer's index date. Generalized linear models were used to compare 12 month disease flares, disease control, and use of medical services in the between cohorts with adjustment for baseline demographics, comorbidities, and resource use. Results: One hundred thirty-one matched pairs of switcher/discontinuers and continuers were analyzed (N = 262); 64% of patients in both cohorts had a diagnosis of CD, and 36% had a diagnosis of UC. The percentage of males was greater in the switcher/discontinuer cohort than in the continuer cohort (64.1% versus 55.0%, P = 0.083); the average age in both cohorts was 38 years. Compared with continuers, switchers/discontinuers had 3 times greater risk of flares (adjusted odds ratio [OR] = 3.23, P < 0.001) and more frequent flares (adjusted incidence rate ratio [IRR] = 1.76, P < 0.001) during the follow-up period. Only 49% of switchers/discontinuers had well-controlled disease symptoms as per the physician, a rate significantly lower (adjusted OR = 0.15, P < 0.001) than continuers (86%). Switchers/discontinuers had 4 times increased risk of having an emergency department visit (adjusted OR = 4.06, P < 0.001) and had more frequent visits to emergency departments (IRR = 4.21, P < 0.001) and outpatient clinics (IRR = 1.11, P = 0.014). Conclusions: Switching or discontinuation of an anti-TNF therapy for non-medical reasons was associated with significantly worse clinical outcomes and increased health care resource use among patients with IBD.